Pemanfaatan Maksim Kuantitas Dalam Interaksi Nonformal Orang Tua-Anak Di Lingkungan Masyarakat Mantingan Kabupaten Ngawi Dan Implikasinya Sebagai Bahan Ajar Di Smk - Wulansari, Nur Ayu, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
The intent and purpose of communicating in the event said embodied in a sentence. This study aims to determine the forms maxim of quantity in a parent-child conversations and benefits as teaching materials in SMK. In this study, the type of research is qualitative descriptive design, source data in this study is a parent-child in the community Mantingan, the data in this study is a sentence that contained a conversation between parent-child. Collecting data in this study refer to the method receipts. The results of research in the form sentences resulting from the interaction or informal speech between parents and children in the community environment Mantingan Ngawi. The method used is equivalent ekstralingual. Based on the results and discussion can be concluded that the speech generated a total of 42 utterances of each speech provide information in accordance with the needs of listeners. In a conversation between parent-child conversations that there is some form of conversation in the form of a question as much as 28 speech, in the form of messenger conversations 6 speech, conversation in the form of order 5 speech, conversations in the form of call-2 narration and conversations in the form of demand 1 tuturran. Results speech of the conversation between the parents of these children can be used as a reference for teachers in teaching. By utilizing every conversation being used by young parents to be used as a text conversation which is then used as teaching materials or teaching materials in learning. Keywords: maxim of quantity, conversations, parent-child, teaching materials.